Enterprise DevOps playbook : a guide to delivering at velocity - Ott, Bill; Pham, Jimmy; Saker, Haluk (O'Reilly Media, 2016)
DevOps may be an evolutionary step beyond the agile methodology, but applying agile practices on a software development team is one thing; mastering DevOps throughout the enterprise is quite another. This playbook, derived from Booz Allen Hamilton's extended experience with several DevOps initiatives, will help you successfully adopt this game-changing system in your organization to address deployment as well as development. Authors Bill Ott, Jimmy Pham, and Haluk Saker provide a practical roadmap that will help you define the steps necessary to meet your DevOps goals. The playbook distills DevOps into seven key practice areas that you can adapt to the DevOps style that best fits your organization. You'll understand how company culture plays a fundamental role in your ability to use DevOps effectively. Develop the team by finding the right people, tuning the company culture, and learning DevOps principles Take a deep dive into each of the seven DevOps practices and gain a better understanding of what they mean to your organization Determine your organization's strengths and weaknesses in each DevOps practice area Create a DevOps pipeline to put your practices into action, and establish a repeatable process for code development and changes Measure your DevOps pipeline to learn where you are, where you're going, and where you should be Bill Ott is a Digital VP in Booz Allen Hamilton's Strategic Innovation Group with responsibility over the Digital Interactive team. He brings 20 years of professional experience in the field, working with government and commercial clients. Jimmy Pham is an avid technologist who's designed, developed, and managed large software solutions for major private and public customers. He's a Chief Technologist at Booz Allen Hamilton, focusing on Modern Software Development. Haluk Saker is a director with the Digital team and a 20-year veteran of Booz Allen. An experienced system/cloud architect, he leads Digital's DevOps practice, microservices architecture, and numerous cloud platforms investments.